Simulação computacional de carreador lipídico nanoestruturado contendo gordura de cupuaçu (Theobroma Grandiflorum) - VIEIRA, Ana Paula Bastos Ferreira (Universidade Federal do Pará, 2019)
The constant evolution of the drug delivery systems boosted the search for new strategies, to obtain potentially promising formulations. Computational simulation and molecular modeling can provide effective contributions to the design and evaluation of complex systems, such as lipid nanocarriers containing natural inputs. In this work, a nanostructured lipid carrier (NLC) was proposed using triacylglycerols of cupuaçu fat and capric/caprylic acid, carnauba wax, tween 80®, pluronic® and an enantiomer of ketoconazole. Experimental tests were carried out to evaluate the crystallinity and thermal events of the lipid mixtures, which demonstrated that the M03 mixture had a lower enthalpy value (-15,17 J/g) and greater widening of the diffractogram peaks, suggesting a lower crystallinity structure. Computational simulations were performed to elucidate 3D structures, to study molecular and electrostatic properties, as well as intermolecular interactions with the drug. The molecular docking of M03 with ketoconazole showed interaction of the hydrogen bond type, with bond distance of 2,62 to 3,50Å and affinity energy of -5,3 Kcal/mol. The three-dimensional CLN model showed good molecular distribution and after simulation of molecular dynamics, the system remained stable (energy -1895,47 KJ / mol), with moderate to weak hydrogen bonding interactions and a distance of 2,45 to 3,50Å. RDF profiles established demonstrate strong interactions between ketoconazole and tween 80, between water and pluronic, between pluronic and SOO, and between tween 80 and SOO, all interactions occurring within the radius ≥2Å of distance. These results can be used as support to guide the future development of a CLN formulation, anticipating the experimental tests and helping to obtain thriving formulations.